Discrepancies of Upper Troposphere Summer Thermal Contrast Between Tibetan Plateau and Tropical Indian Ocean in Multiple Data - Luo, Xiaoqing; Xu, Jianjun; Li, Kai (Frontiers in Environmental Science, 2021)
Under the background of global warming, the summer land-sea thermal contrasts at the upper troposphere exists great discrepancies in radiosonde data (IUK, RICH, RAOBCORE), reanalysis data (JRA-55, NCEP/DOE, ERA5) and CMIP6 models results(MPI, FGOALS, CESM2) for the period of 1979-2014. It can be found that the descriptive statistical indicators(i.e. maximum, minimum, skewness) of the summer land-sea thermal contrasts index(TTI) between the Tibetan Plateau(TP) and the Tropical Indian Ocean (TIO) vary greatly. The ERA5 and JRA-55 data have the best correlation with radiosonde data. The linear trend and running linear trend(RTL) of the radiosonde data are significantly correlated with the reanalysis data, and both show that the land-sea thermal contrast rapidly increasing are in 1990s and the late 2000s, and the period of rapid weakening was early 2000s. This interannual variation may modulated by the decadal signals such as Pacific Decadal Oscillation (PDO). Except for the NCEP/DOE and IUK, other data show that the most significant warming in the TP-TIO region is at the upper troposphere, and the vertical profiles of the summer temperature trend are quite different in different data, and CMIP6 shows an obvious warm bias in the upper troposphere.